Pengaruh Return On Equity (ROE) Dan Debt To Equity Ratio (DER) Terhadap Pertumbuhan Laba Pada PT. Unilever Indonesia,Tbk - Ragil Muhammad Taqwa; Aris Munandar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Profits can be used by companies to run their business and strengthen the company's position in facing competition at the local, national and international levels. The purpose of this study was to determine whether Return On Equity (ROE) and Debt To Equity Ratio (DER) have an influence on profit growth at PT. Unilever Indonesia Tbk during the 2012-2021 period either partially or simultaneously. This type of research includes associative research. The instrument used in this study is in the form of a list of financial statements tables of PT. Unilever Indonesia Tbk. The population used in this study is the financial statements at PT. Unilever Indonesia Tbk for 40 years (1982-2022). The sample is the financial statements for the last 10 years from 2012-2021 which consist of a balance sheet and profit and loss. The sampling technique used is Non Probability Sampling, namely Purposive Sampling. The data analysis technique used to process the data in this study is the Classical Assumption Test, Coefficient of Determination Test, Multiple Linear Regression Analysis Test, Hypothesis Test which consists of F Test (partial) and T Test (simultaneous).